Transformasi Organisasi Keagamaan Melalui Nilai-Nilai Buddhayana: Studi Organisasi Majelis Buddhayana Indonesia - Hanjaya Yusdhika, Aldo WIse; Putri, Adelia Mahayani; Ardianto, Hendri; Suryanadi, Juni; Taridi, Taridi (Kajian dan Reviu Jinarakkhita: Jurnal Gerakan Semangat Buddhayana (Jinarakkhita Review & Studies: Journal of Buddhayana Spirit Movement), 2023)
This study aims to investigate the transformation of religious organizations through the application of Buddhayana values in the context of the Organization Majelis Buddhayana Indonesia. Buddhayana is Buddhism itself. In the context of organizations, Buddhayana as an ideology is instilled by upholding non-sectarian values, universalism, pluralism and belief in Dharmakaya. This research uses the literature study method. Literature study can be taken by collecting references consisting of several previous studies which are then compiled to draw conclusions. The transformation of religious organizations by reinforcing religious values can help deepen the spiritual experience of adherents and increase the organization's positive contribution to society. These values are embodied in "Buddhayana" which is non-sectarian, pluralism, universalism and belief in Dharmakaya